Clinical and angiographic outcome of directional atherectomy followed by stent implantation in de novo lesions located at the ostium of the left anterior descending coronary artery. Issue 9 (15th August 2003) - Airoldi, F; Di Mario, C; Stankovic, G; Briguori, C; Carlino, M; Chieffo, A; Liistro, F; Montorfano, M; Pagnotta, P; Spanos, V; Tavano, D; Colombo, A
Abstract : Background: Lesions located at the ostium of the left anterior descending coronary artery (LAD) are considered an ideal target for directional atherectomy (DCA), but few data are available about the value of using this strategy before stenting in comparison with stenting alone. Objectives: To investigate the immediate and mid term clinical and angiographic results of DCA followed by stent implantation for ostial LAD lesions. Design: Retrospective comparison of the immediate and mid term angiographic and clinical results of a series of 117 consecutive patients with de novo lesions located at the ostium of the LAD. Of these, 46 underwent DCA before stenting and 71 were treated with stenting alone. Results: Technical success in the two groups was similar at around 98%. DCA plus stenting provided a larger minimum lumen diameter at the end of the procedure than stenting alone (3.57 (0.59) mm v 3.33 (0.49) mm, p = 0.022). There were no differences for in-hospital major adverse events (MACE) (7.5% for atherectomy plus stenting, and 5.3% for stenting alone; p = 0.41). All patients had clinical follow up at a mean of 7.9 (2.7) months. Angiographic follow up was done in 89 patients (76%) at a mean of 5.9 (2.2) months. The atherectomy plus stenting group had a larger minimum lumen diameter than the stenting group (2.79 (0.64) mm v 2.26 (0.85) mm, p = 0.004) and a lower binary restenosis rate (13.8% v 33.3%, p = 0.031). Six month MACE were reduced in the atherectomy plus stenting group (8.7% v 23.9%, p = 0.048). Conclusions: Debulking before stenting in de novo lesions located at the ostium of the LAD is safe and is associated with a high rate of technical success. Follow up data show that DCA plus stenting results in a significantly larger minimum lumen diameter and a lower incidence of restenosis than stenting alone.